Holmium Laser Enucleation of the Prostate With Percutaneous Nephrostomy Into the Transplanted Kidney in Patient With Severe Benign Prostatic Hyperplasia With Vesicoureteral Reflux – A Case Report - Nohara, Takahiro (Urol Case Rep, 2015)
A 66-year-old male, who had received renal transplantation 10 years before, was admitted to our hospital with urinary retention. The prostate volume was 169.2 ml. Furthermore, grade 5 vesicoureteral reflux (VUR) was shown in the cystography. Holmium laser enucleation of prostate (HoLEP) was performed, and percutaneous nephrostomy to the transplanted kidney was performed simultaneously to prevent from severe perioperative infection. After that, renal graft function improved and no urinary retention reoccurred, although surgical repair against VUR was necessary 10 months after HoLEP. We conclude that surgical treatment for BPH after kidney transplantation should be strongly considered with care for infections.